An actinomycete isolate from solitary wasp mud nest having strong antibacterial activity and kills the Candida cells due to the shrinkage and the cytosolic loss - Kumar, Vijay; Naik, Bindu; Gusain, Omprakash; Bisht, Gajraj S. (Frontiers in Microbiology, 2014)
An actinomycetes strain designated as MN 2(6) was isolated from the solitary wasp mud nest. The isolate was identified using polyphasic taxonomy. It produced the extensive branched brown substrate and white aerial hyphae that changed into grayish black. The aerial mycelia produced the spiral spore chains with rugose spore surface. The growth was observed between temperature range of 27-37°C, pH 8-10 and below salt concentration of 6% (w/v). The comparative analysis of 16S rRNA gene sequence and phylogenetic relationship showed that strain MN 2(6) lies in clade with Streptomyces hygroscopicus subsp. hygroscopicus NRRL 2387T, Streptomyces sporocinereus NBRC 100766T and Streptomyces demainii NRRL B-1478T with which it shares a 16S rRNA gene sequence similarity of 99.3%. The strain MN 2(6) can be differentiated from type strains based on phenotypic characteristics. The strain MN 2(6) showed most promising activity against Gram-positive, Gram-negative bacteria, acid-fast bacilli and Candida species suggesting broad-spectrum characteristics of the active metabolite. Evaluation of anti-candidal activity of the metabolite of strain MN 2(6) by scanning electron microscopy (SEM) revealed changed external morphology of yeast. It kills the Candida cells due to the shrinkage and the cytosolic loss. However, further studies are required to elucidate the structure of the active metabolite produced by the isolate MN 2(6)